ANALISIS IMPLEMENTASI PROGRAM DANA DESA DALAM MENANGGULANGI PEMUKIMAN KUMUH DI KELURAHAN BELAWAN BAHAGIA, KECAMATAN MEDAN BELAWAN - Hernatha Abigail Hutagalung; Vera Pasaribu; Jonson Rajagukguk (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The issue of slum settlements remains one of the environmental problems in urban areas, including in Belawan Bahagia Subdistrict, Medan Belawan District. The government is attempting to address this problem through various development programs. This study analyzes the implementation of the Village Fund program in tackling slum settlements in Belawan Bahagia Subdistrict using George C. Edwards III's theory. The method used is qualitative through interviews, observation, and documentation. The research results show that the program implementation has gone quite well but is not yet optimal. Community communication and participation are still low, resources are limited, while the disposition of officials and the bureaucratic structure have functioned well. The program contributes to environmental improvement but still requires optimization.